Managing change enquiry and action - Beech, Nic; MacIntosh, Robert (Cambridge Cambridge University Press, 2012)
A case-rich textbook that gives students and managers the tools they need to deal with the messy reality of change.
Part I. Foundations: 1. Practising change management; 2. Current perspectives and classic ideas -- Part II. Diagnosing: 3. Clarity and ambiguity; 4. Engagement and vitality; 5. Stakeholder positioning and dynamics; 6. Culture, habits and unlearning -- Part III. Enacting change: 7. Changing structure; 8. Identity and change; 9. Choosing customers and competitors; 10. Changing processes; 11. Aligning people and activities; 12. Learning and developing; 13. Change through dialogue -- Part IV. Explaining: 14. Developing and interpreting evidence and reflexive learning; 15. Accounting for change; 16. Conclusions -- Part V. Extended cases: Case 1 - ABB; Case 2 - Its Canada; Case 3 - Island Opera; Case 4 - Oticon; Case 5 - Admiral Insurance; Case 6 - Power Provision; Case 7 - Nokia; Case 8 - Her Majesty's Revenue and Customs; Case 9 - Apple.
Includes bibliographical references and index.
Keywords: Organizational change; Organizational change -- Management